(Diptera:Culicidae) Culex quinquefasciatus تقييم فاعلية بعض المستخلصات النباتية في هلاك يرقات الطور الرابع لبعوض - عبد شاكر, هيا (University of Thi-Qar Journal of Science, 2011)
The Present Study has been prepared to evaluate the efficacy of the aqueous , alcoholic Extract and Secondary Compounds of Myristica fragrans , Anabasis setifera , Capparis spinosa , Chenopodium murale , Cordia myxa and Glycyrrhiza glabra on the 4th larval instar of Culex quinquefasciatus , the results showed Significant difference with high mortality percentage rate reached 42.49% for alcoholic extract compared with%11.11 for aqueous extract ,and the alcoholic extract of Chenopodium murale , Myristica fragrans was the most effective extract , with the lethal concentration (LC50) for larvae 501 , 1258 ppm after 48 hour of treatment respectively.During this Study active Compound has been identified from studied Plants by using some chemical reagent ,Alkaloid, Phenol compounds and volatile oil isolated from studied Plants, Alkaloid compounds and volatile oil revealed high activity on mosquitoes larvae in comparing with Phenolic compounds reached to 70.7 ppm (LC50) for Ch. murale alkaloid, Where as the lower activity appeared in Phenolic compound of Capparis spinosa with (LC50) reached 11220 ppm after 48 hr of treatment